Implementasi Green Environment Pondok Pesantren Pph Ar Risalah Dan Lintang Songo Yogyakarta - Siti Aminah; Moh. Abu Suhud (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
This research was motivated by observations in 2021 in two boarding schools, which showed the importance of caring for the environment in boarding schools, which showed the importance of caring for the environment in the context of climate change issues. Data from the Ministry of Environment in 2020 noted that each person produces 2.1 kg of waste per day. Research in 2018 found that every woman in Indonesia throws away around 20 disposable pads per month, which is equivalent to 1.4 billion disposable sanitary napkins per month, which is equivalent to 1.4 billion sanitary napkin waste per year. waste per year. This research aims to explore how to create green awareness in Pondok Pesantren Ar-Risalah Bantul and Lintang Songo Bantul as well as the barriers in its implementation. and the obstacles in its implementation. Using participatory action research (PAR) method, researchers were directly involved in both research locations. The results The results showed that environmental awareness in both boarding schools still vary. Although there are policies and rules, proactive actions are still limited. limited. Both boarding schools have started waste management efforts with their respective potentials: Ar-Risalah has a team of students in charge, while Lintang Songo involves local residents. Key barriers include the need for collaboration, economic development through waste processing, and cooperation with external stakeholders.